Produtos alternativos para proteção e indução de resistência à mancha angular em plantas de feijão - (:unkn) unknown (Universidade Estadual de Ponta Grossa, 2022)
The common bean (Phaseolus vulgaris) is a legume of great prominence in the production and consumption of grains in Brazil. Among the factors that lead to a reduction in its productivity, angular leaf spot (Pseudocercospora griseola) is a disease capable of leading to damage and losses in the crop. The study of alternatives to control this disease can bring positive and environmentally sustainable results. The objective of this study was to evaluate the efficiency of fungi of the genus Trichoderma in the bean crop, under in vitro conditions, in a greenhouse and field, against the pathogen P. griseola and to evaluate the effect of these products in the induction of resistance in treated plants, through the activity of peroxidase, polyphenoloxidase and phytoalexin phaseolin enzymes. Seven species of Trichoderma were evaluated in vitro, in three different tests, to verify the antagonism and action of volatile and non-volatile metabolites on the growth and sporulation of P. griseola. In a greenhouse and in the field, the species of Trichoderma, the acibenzolar-S-methyl (ASM) resistance inducer and the fungicide fentin hydroxide were evaluated on the severity of angular leaf spot. In the enzymatic tests, the same treatments evaluated in the field were used and the effect of these products on the induction of resistance in plants treated via foliar was verified, through the activity of the enzymes peroxidase, polyphenoloxidase and phytoalexin phaseolin. In in vitro tests, P. griseola showed a reduction in mycelial growth and sporulation when subjected to fungi of the genus Trichoderma. Under greenhouse conditions, for the cultivar IPR-Tuiuiú, in the second experiment, treatments with T. tomentosum, T. viride and ASM were efficient in reducing the severity of angular leaf spot. Alternative products based on spores of fungi of the genus Trichoderma and ASM, applied to the bean crop under field conditions, were as efficient as the fungicide in reducing the severity of angular leaf spot. The treatments containing T. asperellum, T. endophyticum, T. lentiforme and T. tomentosum were able to promote accumulation of the peroxidase enzyme when compared to the control and to ASM in the evaluated times. For polyphenoloxidase, in the cultivar IPR-Tuiuiú, treatments with Trichoderma did not influence the accumulation of this enzyme, while ASM showed an ascending accumulation over time. In the cultivar IPR-Quero-Quero, there was accumulation of polyphenoloxidase in the treatment with T. harzianum, but showing a tendency to decrease after 48 hours.
Keywords: Phaseolus vulgaris; Pseudocercospora griseola; Trichoderma spp; fungos sapróbios; acibenzolar-S-metílico; Phaseolus vulgaris; Pseudocercospora griseola; Trichoderma spp; saprobic fungi; acibenzolar-S-methyl; CNPQ::CIENCIAS AGRARIAS::AGRONOMIA